Gigantism of infrastructure and urban microsystems The role of the project - Falzetti, Antonella (TeMA - Journal of Land Use, Mobility and Environment, 2012)
If there is a solidarity between nature and landscape, not so reassuring is ’the relationship between landscape and infrastructure, or landscape and urbanized areas, too often based on functional reasons that do not provide ’ the value of natural places and ’the needs of vulnerable urban areas as well.